Comparison of 30 mCi and 50 mCi I-131 doses for ablation of thyroid remnant in papillary thyroid cancer patients. (2nd January 2018) - Cai, Xiao Yue; Vijayaratnam, Niranjan; McEwan, Alexander J. B.; Reif, Rebecca; Morrish, Donald W.
ABSTRACT: Purpose of the study : To compare efficacy of thyroid remnant ablation using 30 mCi or 50 mCi 131-I in papillary thyroid cancer patients.Materials and methods : Five hundred and fifteen consecutive patients with Tumor-Node-Metastasis (TNM) stages T1-T3 N1/N0/NX receiving either 30 mCi or 50 mCi I-131 were analyzed for the effectiveness of remnant ablation using rhTSH-stimulated serum thyroglobulin. One hundred and five consecutive patients receiving 100 mCi I-131 were analyzed for the incidence of radiation thyroiditis and sialadenitis.Results and conclusions : Doses of 30 mCi and 50 mCi were equally effective for low- and moderate-risk disease but 30 mCi was less effective for T1T2NX disease, and 50 mCi was less effective for T3 compared to T1T2 disease. Low dose radiation hypersensitivity or unknown more extensive disease may have accounted for observed differences. Radiation thyroiditis and sialadenitis were more common in a comparison series of 100 mCi dose compared to 30 mCi, but not more common than in 50 mCi doses.